PENDEKATAN KEARIFAN LOKAL UNTUK MENINGKATKAN KEMAMPUAN APRESIASI SENI MAHASISWA PENDIDIKAN GURU SEKOLAH DASAR FKIP UNIVERSITAS RIAU - Antosa, Zariul (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2014)
The problem in this study was the lack of ability to appreciate the art works on PGSD FKIP-UR students that could be seen from the ability to distinguish works of craft and art works. The students had low ability to explain the function and meaning of craft objects in public life in accordance with the local culture. They had also lack of awards both morally and materially to the creation of creative crafts. They had lack of ability in the understanding of concepts, reasoning, and problem solving art crafts. Based on the problems it was necessary to find away to solve those problems. The teaching methods were needed to be changed. In this study, the researcher applied local wisdom approach. This research was conducted in two cycles, in which each cycle consisted of two meetings. The application of local wisdom approach involved a conscious effort to engage students actively and creatively. Subjects in this study were fourth semester PGSD FKIP-UR students. Research data collection instruments consisted of observation activity sheets and sheets of faculty and students to replay the end of the test cycle. The study was a classroom action research (CAR). This study aimed to increase art appreciation fourth semester PGSD FKIP-UR students. The results of this study indicated that the application of local wisdom approach improved PGSD FKIP-UR students’ art appreciation, with the average value of the initial score 58,41into 84,75 in the second cycle. The average value of faculty activity sheet also increased from an average score 68,15 into 94.75. Students’ activities also increased from an average score 63,24% in the first cycle to 89.80%. Thus, the research hypothesis, if applying local wisdom approach, the ability of PGSD FKIP-UR students to approach art appreciation increased, was proven.Key words: local wisdom, art appreciation